1999
DOI: 10.7326/0003-4819-130-6-199903160-00014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension after Splenectomy?

Abstract: Patients who have had splenectomy may be at increased risk for developing pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
7

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 8 publications
4
112
1
7
Order By: Relevance
“…The association of splenectomy and CTEPH, especially in nonoperable disease, has previously been described [8,9,20]. Several potential mechanisms for this phenomenon have been postulated, including loss of splenic function leading to the circulation of platelet-derived mediators, which, when acting in conjunction with abnormal erythrocytes, promote thrombus formation in the pulmonary circulation [9].…”
Section: Discussionmentioning
confidence: 99%
“…The association of splenectomy and CTEPH, especially in nonoperable disease, has previously been described [8,9,20]. Several potential mechanisms for this phenomenon have been postulated, including loss of splenic function leading to the circulation of platelet-derived mediators, which, when acting in conjunction with abnormal erythrocytes, promote thrombus formation in the pulmonary circulation [9].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, scleroderma and lupus are associated with a reduction in peripheral CD4+CD25+ cells, the putative Treg population [23][24][25]. Furthermore, PAH has been described following splenectomy [29]. Finally, it was recently reported that a patient with autoimmune polyendocrinopathy-candidiasisectodermal dystrophy, which is caused by a mutation leading to the loss of function of the autoimmune regulator (AIRE) protein, died with fatal IPAH [30].…”
Section: Pah: Autoimmunity and Immunoregulationmentioning
confidence: 99%
“…Splenectomy is widely performed for treating various hematological and non-hematological conditions [1][2][3][4][5][6]. There are debates as to whether there is increased risk of pulmonary arterial hypertension (PAH) following splenectomy either as a result of increased thromboembolism [7] or due -tion function [8].…”
Section: Introductionmentioning
confidence: 99%